Revealing the Defect-Dominated Electron Scattering in Mg3Sb2-Based Thermoelectric Materials - Jucai Jia; Yan Zhou; Xiaoxi Chen; Wenhua Xue; Hulei Yu; Jing Li; Shizhen Zhi; Chen Chen; Jian Wang; Shuaihang Hou; Xingjun Liu; Yumei Wang; et al. (Research, 2022)
The thermoelectric parameters are essentially governed by electron and phonon transport. Since the carrier scattering mechanism plays a decisive role in electron transport, it is of great significance for the electrical properties of thermoelectric materials. As a typical example, the defect-dominated carrier scattering mechanism can significantly impact the room-temperature electron mobility of n-type Mg3Sb2-based materials. However, the origin of such a defect scattering mechanism is still controversial. Herein, the existence of the Mg vacancies and Mg interstitials has been identified by synchrotron powder X-ray diffraction. The relationship among the point defects, chemical compositions, and synthesis conditions in Mg3Sb2-based materials has been revealed. By further introducing the point defects without affecting the grain size via neutron irradiation, the thermally activated electrical conductivity can be reproduced. Our results demonstrate that the point defects scattering of electrons is important in the n-type Mg3Sb2-based materials.